Research on Forced Vibration Model of End Effector Under Low-Frequency Excitation and Vibration-Suppression Technology - Changqi Li; Henan Song; Ruirui Li; Jianwei Wu; Xiaobiao Shan; Jiubin Tan (Micromachines)
The positioning accuracy of the end effector is the core index that affects the robot’s performance. However, to achieve lightweight and functional requirements, the construction of end effectors is becoming more complex. Lightweight design through slotting is becoming more common. This leads to the fact that the traditional mathematical model cannot accurately characterize the vibration of the end effector. This study proposed the multi-stepwise beam model. It employed the separation of variables and element transmitting method to obtain the mathematical model of the modal shape functions and the natural frequencies. Meanwhile, the vibration response of the end effector under fixed-end excitation was analyzed, and the conclusions were made through experimental research. The direct inverse controller was presented to achieve vibration suppression. The experimental results indicate that the amplitude suppression rate reaches 50%. The system’s equations of motion were solved numerically to analyze the exact relationships for the response and excitation of the beam considered.